2013
DOI: 10.1088/1367-2630/15/5/053042
|View full text |Cite
|
Sign up to set email alerts
|

Stress redistribution in individual ultrathin strained silicon nanowires: a high-resolution polarized Raman study

Abstract: Strain nano-engineering provides valuable opportunities to create high-performance nanodevices by a precise tailoring of semiconductor band structure. Achieving these enhanced capabilities has sparked a surge of interest in controlling strain on the nanoscale. In this work, the stress behavior in ultrathin strained silicon nanowires directly on oxide is elucidated using backgroundfree, high-resolution polarized Raman spectroscopy. We established a theoretical framework to quantify the stress from Raman shifts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Raman back-scattering from a (001) silicon surface allows only the longitudinal optical (LO) mode to be observed [56], while using a high NA objective with small spot size allows measurement of the two transverse optical (TO) modes as well [54]. Although Tarun et al showed that prestrained SiNWs retain a complex strain distribution when patterned on oxide [54], only uniaxial strain is expected to remain after suspension of the SiNWs, whereby the free surfaces of the SiNW are allowed to relax. Gridlines for uniaxial elastic strain in intervals of 0.5% are plotted in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman back-scattering from a (001) silicon surface allows only the longitudinal optical (LO) mode to be observed [56], while using a high NA objective with small spot size allows measurement of the two transverse optical (TO) modes as well [54]. Although Tarun et al showed that prestrained SiNWs retain a complex strain distribution when patterned on oxide [54], only uniaxial strain is expected to remain after suspension of the SiNWs, whereby the free surfaces of the SiNW are allowed to relax. Gridlines for uniaxial elastic strain in intervals of 0.5% are plotted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For SiNWs below 15 nm, quantum confinement begins to have an observable effect, causing peak shifts and asymmetric peak broadening [51][52][53]. It is also known that strain, depending on the crystal direction, can be related to peak shifts for the different optical mode phonons [54][55][56]. Much of the work done using Raman on SiNWs has been on chemically synthesized or chemically etched SiNWs, which typically * daniel.fan@psi.ch exhibit a size, position, and orientation distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The autofocusing system proved to be invaluable as the detected TO signal was very weak especially for the 30 nm nanowires. Characterization of the anisotropic stress relaxation by both LO [3] and TO [4] phonon modes was performed. It was found that both cases suggest a complex redistribution of stress within the nanowire, which is contrary to the prevalent belief that stress is fully relaxed along the narrow width of the nanowire [5].…”
Section: Resultsmentioning
confidence: 99%
“…Recent progress in probing the strain distribution in nanostructures includes utilizing Raman spectroscopy, transmission electron microscopy (TEM) based techniques, and x‐ray diffraction based techniques, such as microbeam x‐ray diffraction, high resolution x‐ray diffraction, and grazing incidence x‐ray diffraction (GIXRD) . Raman spectroscopy provides a fairly good spatial resolution and does not require any specific sample preparation, but it is limited to bare Si structures as the top metallic layer in the device prohibits the laser penetration.…”
Section: Strain Distribution In Silicon‐on‐insulator (Soi) Structuresmentioning
confidence: 99%